Impact of Social Cognition on the Self-Rated Health of the Elderly and Its Mechanisms: Evidence From China’s Comprehensive Social Survey - Liu, Yuan; Hu, Yuqun; Nan, Yan (Frontiers in Psychology, 2022)
Whether and how the differentiated social cognition of the elderly affects their self-rated health has not been deeply discussed. Based on social cognition theory and Chinese situation, this study constructs the social cognitive dimension of Chinese elderly including social attitude, class identity and perception of social relations. Using the data from Chinese General Social Survey in 2017, this study screens out 1728 elderly people aged 60 and over, and discusses the impact mechanism of social cognition on self-rated health of Chinese elderly people aged 60 and over by the construction of structural equation model and mediation effect test method. The results show that social attitude, class identity and perceptions of social relationships have significantly positive effects on the self-rated health levels of elderly individuals. Among them, the path coefficient of social attitude to self-rated health was 0.049, the path coefficient of class identity to self-rated health was 0.171, and the path coefficient of social relationship perception to self-rated health was 0.248; both class identity and perception of social relationship have significant mediating effects on elderly self-rated health through social engagement. This study shows that social cognition rarely studied in existing literature has significant effects on the self-rated health of older adults, providing fruitful insights for enhancing the self-rated health level of elderly individuals.